Identification of Rodent Species That Infest Poultry Houses in Mafikeng, North West Province, South Africa - Ramatla, Tsepo; Mphuthi, Nthabiseng; Gofaone, Kutswa; Taioe, Moeti O.; Thekisoe, Oriel M. M.; Syakalima, Michelo (International Journal of Zoology, 2019)
Rodents cause serious adverse effects on farm production due to destruction of food, contamination of feed, and circulation of diseases. The extent of damage or the diseases spread will depend on the type of rodents that invade the farm. This study was conducted in order to find out the species of rodents that infest poultry farms around Mafikeng, North West Province of South Africa. The study was part of a broader project that was investigating Salmonella vectors in the poultry farms around the province. The study trapped 154 rodents from selected farms and used the Cytochrome oxidase subunit 1 (COI) and the Cytochrome b (Cyt-b) barcoding genes for species identification. Two rodent pest species, namely, Rattus rattus (the black rat) and Rattus tanezumi (the Asian Rat/Asian House Rat) were identified. A total of 99 (64.3%) were identified as Rattus rattus and 55 (35.7%) were Rattus tanezumi. Between the two target genes, Cyt-b gene was only able to identify 40 (25.97%) of the total samples while COI was more efficient and amplified all the samples and thus was a better target gene for this kind of identification. The two rat species identified are known vectors of serious diseases; thus their presence should be regarded as an indication of high risk for diseases. Despite having been detected in the country before, finding R. tanezumi as the second largest rat species in the area was unexpected since this species is known to be indigenous to Asia.